Microcredit supply and credit rationing in a developed country: a theoretical model and empirical evidence - Barros, C.; Lagoa, S.; Leão, E. (Transformations in Business and Economics, 2014)
Microcredit has been proposed as a tool for poverty reduction. However, little is known about how banks determine loans terms and whether credit supplied is enough to satisfy demand This paper, firstly, proposes a theoretical model to analyse microcredit interest rates and amounts. Secondly, the model predictions regarding loans' size are tested using a disequilibrium model and data from a developed country with a growing market. It is found that banks actively adjust loan amount to client and macroeconomic risks, and that credit rationing was high, even though declining as the market developed. Finally, policy implications are suggested.